Comprehensive Study of Beej, Beejbhag and Beejbhagavyav w.s.r Genetics – A Review Article. - Kumari, Priyanka; Mishra, Vikas; Guddu, Birendra Kumar; Gupta, Shyam Sundar (International Research Journal of Ayurveda & Yoga, 2023)
Genetics is the science of genes, genetic variation and heredity in the organism. Genetics is thought to be a new branch of science evolved during 19th century. Gregor Mendel was the first who developed principle of inheritance and had described the transmission of genetic traits from generation to generation. Although some concepts of genetics have been described in Ayurveda which is Upaveda of Atharvaveda and thousands of years old texts. Ayurveda has been cited the concepts of Beeja, Beejbhag, Beejbhagavyava which influence the prakriti of individual and vitiation of these units cause deformity in the progeny. Acharya Charaka, Sushrut and Vagbhata all have described many genetic deformities in Sharir sthan. All three Acharyas of our Brihattraye have brief description about formation of foetus, growth of foetus, foetal deformity, disorders of pregnancy, Adibalapravritta disease etc.